Immobilization of Oxyanions on the Reconstructed Heterostructure Evolved from a Bimetallic Oxysulfide for the Promotion of Oxygen Evolution Reaction - Yu, Kai; Yang, Hongyuan; Zhang, Hao; Huang, Hui; Wang, Zhaowu; Kang, Zhenhui; Liu, Yang; Menezes, Prashanth W.; Chen, Ziliang (Nano-Micro Letters, 2023)
Efficient and durable oxygen evolution reaction (OER) requires the electrocatalyst to bear abundant active sites, optimized electronic structure as well as robust component and mechanical stability. Herein, a bimetallic lanthanum-nickel oxysulfide with rich oxygen vacancies based on the La2O2S prototype is fabricated as a binder-free precatalyst for alkaline OER. The combination of advanced in situ and ex situ characterizations with theoretical calculation uncovers the synergistic effect among La, Ni, O, and S species during OER, which assures the adsorption and stabilization of the oxyanion (SO42−) onto the surface of the deeply reconstructed porous heterostructure composed of confining NiOOH nanodomains by La(OH)3 barrier. Such coupling, confinement, porosity and immobilization enable notable improvement in active site accessibility, phase stability, mass diffusion capability and the intrinsic Gibbs free energy of oxygen-containing intermediates. The optimized electrocatalyst delivers exceptional alkaline OER activity and durability, outperforming most of the Ni-based benchmark OER electrocatalysts. Highlights: 1 A bimetallic lanthanum-nickel oxysulfide based on a La2O2S prototype was developed as a precatalyst for the electrochemical alkaline oxygen evolution reaction (OER). 2 The in situ, ex situ, and theoretical investigations demonstrated that the precatalyst underwent a deep OER-driven reconstruction into a porous heterostructure where NiOOH nanodomains were uniformly separated and confined by La(OH)3 barrier. 3 Oxyanion (SO42−) was steadily adsorbed on the surface of this in situ reconstructed NiOOH/La(OH)3 heterostructure, enabling it for enhanced OER activity and durability.